Use of the Tiktok Application to Reduce Teen Verbal Aggression in OSM, Ambon City - Neleke Huliselan; Prisca Diantra Sampe (Peneliti.net, 2022)
The purpose of this study was to determine the description of verbal aggression in adolescents at OSM, Ambon City and to formulate and develop a module for using the tiktok application to reduce adolescent verbal aggression in OSM, Ambon City. The research and development procedure is based on this research to produce a module for using the tiktok application. In general, this type of research uses quantitative research. The results show that adolescent verbal aggression in OSM, Ambon city is in the moderate category (94%). Of the five aspects, the lowest is the aspect of empathy and the highest is the coding aspect of verbal aggression messages. The overall results of the validation test show that this module is at a score of 0.98, which means the module for using the tiktok application to reduce adolescent verbal aggression in OSM, Ambon City is in the moderate category.